Avaliaçao agronômica do gênero Cratylia na regiao semi-árida do Brasil - Sousa, Francisco Beni de; Oliveira, Martiniano Cavalcante de (International Center for Tropical Agriculture, 1996)
The semiarid region of northeastern Brazil covers approximately 100 million hectares, and its cattle raising and goat production play an important role in the country's economy. Among the native plants of the region, the "camaratuba" (Cratylia mollis Mart.) is a legume of high nutritive quality for ruminants, contributing up to 18 percent of ruminant diets. After 12 years of cultivation and evaluation, this legume still persists in experimental plots at the Centro de Investigaciones del Trópico Semiárido in northeastern Brazil